2014
DOI: 10.1111/maq.12095
|View full text |Cite
|
Sign up to set email alerts
|

“I Didn't Feel Like I Was a Person Anymore”: Realigning Full Adult Personhood after Ostomy Surgery

Abstract: Colorectal cancer (CRC) is the third most common cancer in the United States. For some CRC patients, cancer treatment involves creating a permanent or temporary intestinal ostomy. Having an ostomy often results in complex social and physical concerns—including unpredictable and at times publicly noticeable bowel output. In this article, we discuss findings from 30 in-depth interviews with female CRC survivors with ostomies in the western United States. We highlight how having an ostomy disrupts culturally sanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 41 publications
(75 reference statements)
2
47
0
7
Order By: Relevance
“…Our work complements and extends previous research which suggested people with an ileostomy report post-operative pain, shock at the physical impact of surgery, vigilance with regard to bodily functions and the working of the appliance (Danielsen et. al., 2013a;Kelly, 1992;Ramirez, 2014;Notter & Burnard, 2006). What our analysis adds is: closer analysis of participants' explicit attendance to changing sense of self, more detailed delineation of some of the psychological processes involved and consideration of the range of possible impacts on identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work complements and extends previous research which suggested people with an ileostomy report post-operative pain, shock at the physical impact of surgery, vigilance with regard to bodily functions and the working of the appliance (Danielsen et. al., 2013a;Kelly, 1992;Ramirez, 2014;Notter & Burnard, 2006). What our analysis adds is: closer analysis of participants' explicit attendance to changing sense of self, more detailed delineation of some of the psychological processes involved and consideration of the range of possible impacts on identity.…”
Section: Discussionmentioning
confidence: 99%
“…Three which come quite close to ours in terms of research question and orientation are: Danielson et al (2013a), Ramirez et al (2014), Kelly (1992) interviews. This does indeed show the complexity of comparing across studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The wider set of articles concerned with meanings and experiences of cancer diagnosis, treatment and the spread or recurrence of cancer also focused on how people living with the effects of cancer surgery realigned personhood (Ramirez et al . ), regained wholeness (Crompvoets ) and in some cases integrated test results into ‘technoscientific illness identities’ (Bell and Kazanjian , Jordens et al . , Sulik ).…”
Section: Living With and Beyond Cancermentioning
confidence: 99%
“…7 Our previous research suggests that permanent ostomies are associated with body image disturbance, sexual dysfunction, and relationship problems, resulting in poor overall HRQOL. 815 …”
Section: Introductionmentioning
confidence: 99%